Association of mental health help-seeking with mental health-related knowledge and stigma in Japan Rugby Top League players - Ojio, Y.; Matsunaga, A.; Yamaguchi, S.; Hatakeyama, K.; Kawamura, S.; Yoshitani, G.; Horiguchi, M.; Nakajima, S.; Kanie, A.; Horikoshi, M.; Fujii, C. (PLOS ONE, 2016)
Background: Globally increasing clinical and research interests are driving a movement to promote understanding and practice of mental health in elite athletes. However, few studies have yet addressed this issue. This study aims to describe the association of the intention to seek help with mental health knowledge and stigma and the severity of depressive symptoms in Japan Rugby Top League players. Methods: As a target population, we studied 233 Japan Rugby Top League male players (25-29 years = 123 [52.8%]), who were born in Japan, using a cross-sectional design. Surveys were conducted using anonymous, web-based self-administered questionnaires. Structural equation modelling was performed to evaluate the hypothesis of an interrelationship between mental health knowledge, stigma, and severity of depressive symptoms as factors influencing the intention to seek help. Results: Players with more severe depressive symptoms were more reluctant to seek help from others (ß = - 0.20, p = 0.03). Players with greater knowledge about mental health tended to have less stigma toward others with mental health problems (ß = 0.13, p = 0.049), but tended not to seek help with their own mental health problems. Conclusions: Rugby players in need of mental health support, even with greater knowledge, tend not to seek help from others, while having less stigma toward people with mental health problems. Rugby players might require approaches other than a knowledge-based educational approach to encourage them to seek help.